The Strengthening Family On Marriage Planning Among Adolescent Women at Rural Area - Maurida, Nurul; Basri, Achmad Ali (Jurnal Kesehatan dr. Soebandi, 2025)
Marriage planning for adolescent women in rural areas is one of needed to be considered to prevent adolescent women from early marriage, the majority of which have a negative impact on them. Families in rural areas need to have a strengthening family to prepare adolescent women’s marriage. The purpose was to analyze the influence of strengthening families on marriage planning among adolescent women in rural areas. The research location is in one of the rural areas in Jember Regency. The research design uses a quantitative descriptive approach. The research population was mothers with adolescent women aged 13-18 years and mothers who lives in village. The research respondent was 260 used simple random sampling technique. The independent variables consisted parental resilience, social connection, knowledge of parenting, concrete support, social and emotional competence. The dependent variable was marriage planning. The research instrument was a questionnaire with closed questions. Multivariate analysis used multiple linear regression tests. The results showed that there was partial influence of parental resilience (p=0.000), social competence (p=0.000), knowledge of parenting (p=0.000), and social and emotional competence (p=0.045) on marriage planning. There was no partial influence of concrete to support (p=0.278) on marriage planning. The R square value was 0.795. The F test showed p<0.001 with F value = 196.724. This showed that there was a simultaneous influence between parental resilience, social connection, knowledge of parenting, concrete of support and social and emotional competence on marriage planning. Parental salience is the most influential variable in strengthening families. Families in rural areas need to improve managing stress and implementing family functions to prepare adolescent women’s marriages